«Future War»: the experience of analytical foresight of military conflict by Red Army intelligence practitioners - I. V. Fedotova (Омский научный вестник: Серия "Общество. История. Современность", 2022)
The publication analyzes the content of one of the first domestic predictions in the field of geopolitics – the information and analytical work «The Future War», prepared in 1928 by specialists of the IV (intelligence) Directorate of the Red Army Headquarters under the leadership of the Chief of Staff of the Red Army M. N. Tukhachevsky. The history of the creation of the work is presented, the accuracy of the forecasts proposed by theorists is analyzed, and the modern relevance of this study is revealed in the light of the current global geopolitical situation, when Russia, as in the 1920s, is opposed by a block of unfriendly states.